Features of the formation of Arabic diplomatic terms - Matevosyan, Ara (Bulletin of Yerevan University B: Philology, 2021)
The Arabic language of diplomacy, as terminological sub-language with special vocabulary, stands out with features as accuracy, solemnity, politeness, etc. This terminological sub-language consists of many professional terms that are understood only by specialists of the field. The system of Arabic diplomatic terminology is supplemented with new terms through borrowings from different languages, translations, as well as a number of lexical-semantic, syntactic and morphological-syntactic methods of word formation in Arabic.
Keywords: term; terminology; Arabic diplomatic language; borrowing; calquing; word formation; translation; grammatical method; syntactic method; lexical-semantic method